A study on customers satisfaction of stage bus fares and services in Kuching, Sarawak / Jaafar Pyeman ... [et al.] - Pyeman, Jaafar; Ali, Jati Kasuma (2004)
The purpose of this paper was to investigate the customers' perception with regards to the public stage bus transportation service in Kuching, Sarawak. The customers perception towards the quality of the services was transformed into specific customer satisfaction index. There were two main aspects explored in this study in providing data for customer satisfaction index computation namely the customers satisfaction level based on twelve (12) criteria and the importance level of the satisfaction criteria based on the different priority given by the customers. Questionnaires were distributed to the respondents who were the users of the public stage bus service in Kuching, Sarawak.